2018
DOI: 10.1108/tr-11-2017-0175
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the hotel selection factors of vegetarians: the case of Turkey

Abstract: Purpose The purpose of this study was to investigate the hotel selection preferences of vegetarians in Turkey. Design/methodology/approach The questionnaire used in this study had four main sections: animal and environmentally friendly hotel attributes; hotel features and facilities; hotel food and beverage services; and demographic and travel information of respondents. Data were collected by way of face-to-face questionnaires from 328 self-identified vegetarians who visited the first vegan/vegetarian event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
2
17
0
6
Order By: Relevance
“…In this case study, most of the participants are vegan/vegetarian and the provision of vegan food in this VT has resolved the embarrassment and inconvenience vegetarians faced during travel before (Dewan, 2017). In the normal tour, vegetarians might not be able to find restaurants providing meat‐free meals (Dilek & Fennell, 2018; Rivera & Shani, 2013). Rather, the VT investigated in this study allowed travelers to relax and enjoy their visit without having to bring their own food or worrying about the quality of vegan food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case study, most of the participants are vegan/vegetarian and the provision of vegan food in this VT has resolved the embarrassment and inconvenience vegetarians faced during travel before (Dewan, 2017). In the normal tour, vegetarians might not be able to find restaurants providing meat‐free meals (Dilek & Fennell, 2018; Rivera & Shani, 2013). Rather, the VT investigated in this study allowed travelers to relax and enjoy their visit without having to bring their own food or worrying about the quality of vegan food.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Rivera and Shani (2013) found that some restaurants are still unaware of the special needs of vegetarian tourists (e.g., a better-designed menu that explicitly marks vegetarian items). In hotel selection, vegetarians give priorities to those environmentally and animal-friendly hotels, which can be indicated by facilities, food, and beverages in the hotels (Dilek & Fennell, 2018).…”
Section: Difficulties Faced By Vegetarian/vegan Consumersmentioning
confidence: 99%
“…The approximately 800,000 km 2 area and strategically located nation is one of Europe and Middle East's largest countries, thus making Turkey one of the most important travel destinations in the world (Göymen, 2000;Yolal, 2016). However, the modern world tourism market is known to be largely affected by many factors (Dilek & Fennell, 2018;Tohmo, 2018). Some of these factors are characterized by shocks (uncertainty) that target the tourism sector and other economic activities that directly affects consumer decisions, such as changes in disposable income, advertising campaigns, and unexpected factors, such as terrorist attacks (Balli, Shahzad, & Uddin, 2018;Gozgor & Ongan, 2017;Ongan & Gozgor, 2018;Wu & Wu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Killing a plant involves less feelings of guilt than killing an animal. Vegetarianism is hence considered morally superior to the consumption of animals (Dilek and Fennell, 2018).…”
Section: Plants As a Life Formmentioning
confidence: 99%